In silico Analysis of TCR Vβ7 of Two Patients with Type 1 Diabetes Mellitus - Zhou, Jianwei; Kong, Cui; Wang, Xiukui; Jia, Yinfeng; Wang, Li; Chang, Hong; Sun, Lin (Journal of Laboratory Physicians, 2013)
Objective: To compare the sequences and crystal structures of variable region of beta chain 7 (Vβ7) of T cell receptor (TCR) of two patients with type 1 diabetes mellitus (T1DM).Patients and Methods: The skewness of TCR Vβ7 of two T1DM patients were detected with real-time florescence quantitative polymerase chain reaction (FQ-PCR) and deoxyribonucleic acid (DNA) melting curve analysis technique followed by being sequenced, the crystal structures of them were simulated according to CPH models 2.0 Server, IMGT database, and RasMol 2 software.Results: The whole sequences of TCR Vβ7 of T1DM patient-1 were "CASRTAGQYEQYFGPGTR", that of patient-2 were "CASRTAGQYEQFFGPGTR"; the only difference between them lied on the 12th amino acid. The crystal structures of Vβ7 of the two patients simulated with backbone model were rather similar, while that with sphere model were obviously different.Conclusion: Although the TCR Vβ7 of the T1DM patients share the similar gene sequences, their crystal structures simulated with sphere model are different, and the mechanism needs further study.
Keywords: Beta chain; crystal structure; T cell receptor; type 1 diabetes mellitus; variable region